Becoming a Christian Minangkabau in Indonesia: The Struggle Between Identity and Religious in the Land of Migration - Jufri Naldo; Arifki Budia Warman; Fitriani Fitriani; Syahrial Arif Hutagalung; Benny Ridwan; Muhammad Abduh Isma; Fazli Rachman (Jurnal Ilmiah Peuradeun, 2026)
This study aimed to explore the experiences of Minangkabau individuals who converted to Christianity and to analyze how they negotiate ethnic identity, social belonging, and family relationships after religious conversion. Employing a qualitative approach, data were collected through in-depth interviews with eight Minangkabau converts residing in Yogyakarta, Jakarta, Medan, Ambon, and Makassar and were analyzed using thematic analysis. The findings revealed that conversion occurred through diverse pathways, including interfaith marriage, emotional attachment, personal conviction, and prolonged interaction within religiously diverse environments. Despite experiencing varying levels of family resistance and social exclusion, participants continued to maintain kinship ties, cultural attachments, and a strong sense of belonging to the Minangkabau community. The study demonstrated that religious conversion did not necessarily diminish ethnic identity but instead generated an ongoing process of identity negotiation and social adaptation. These findings contribute to the anthropology of religion and identity studies by showing that cultural belonging can persist despite significant religious transformation, giving rise to what this study conceptualizes as a “New Minangkabau” identity in increasingly plural social contexts.